El Salvador : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper assesses the potential output in El Salvador. Based on various filters and the production function approach, El Salvador's potential growth is estimated at about 2 percent for 1999-2015, and the output gap is now virtually closed. Potential growth after the global financial crisis has fallen as a result of lower capital accumulation and total factor productivity (TFP). TFP growth depends on technological progress, as well as the institutional, regulatory, and legal environment in which businesses operate. From a cyclical perspective, the economy is assessed to be operating at potential and labor market conditions also appear to be broadly neutral. Strengthening capital and TFP growth going forward is critical to achieve the authorities' goal of raising potential growth to 3 percent over the medium term. Structural reforms should prioritize mobilizing domestic savings to invest and build a higher capital stock, enhancing research and development/technological diffusion and competition in product and labor markets, strengthening institutions to secure property rights and reduce red tape, improving infrastructure, facilitating access to financing, and fostering human capital to boost TFP growth. Going forward, it is critical to undertake structural reforms to strengthen capital and TFP to raise potential growth.